pH Effect on Microbial Corrosion by Pseudomonas Aeruginosa Sp. on Galvanized JIS3502 Steel - Nur Syuhada, A. (Trans Tech Publications Ltd, 2022)
Microorganisms can initiate, accelerate, and/or inhibit corrosion processes through several different ways, including modification of the localized environment at the metal/solution interface causing pitting attack. In this work, the effect of pH on Pseudomonas growth was investigated in understanding the biodeterioration manganese steel rod due to bacteria attack. This study focused on identifying the effect of pH on the corrosion of galvanized steel. In artificial seawater containing Pseudomonas Aeruginosa. Galvanized steels were exposed to the medium for 7 days at 37Â°C at pH ranging from 5.0 to 9.0. Roles of different metallurgical, chemical and microbiological features on the surface will be reviewed to interpret this phenomenon. The results confirmed that the pits formed in this case are attributed to the Pseudomonas Aeruginosa sp under microbial corrosion. Â© 2022 Trans Tech Publications Ltd, Switzerland.